Znacimye komponenty obšcej i special'noj podgotovlennosti vysokokvalificirovannych sportsmenov, specializirujušcichsja v pulevoj i stendovoj strel'be - Tarasova, L. V.; Abramova, T. F.; Nikitina, T. M.; Timakova, T. S.; Pankov, V. A.; Vorobyov, S. M. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
In the process of pedagogical research the indicators of general and special training of elite athletes specializing in bullet and bench shooting in the competitive stage of the training macrocycle are determined. The importance of indicators of General and special training of elite athletes specializing in bullet and bench shooting in the competitive stage of the macrocycle is determined. The most significant components of general preparedness in bullet and boom shooting include: a change in the component composition of the body (increase in fat mass in men, decrease in muscle mass in women of the discipline rifle); optimization of vegetovascular function (SBP, DBP and heart rate); the functioning of the cardiovascular system, the tension of regulatory mechanisms and the reserve functions of the cardiovascular system; duration of breath holding in the Genchi test; respiratory respiration; lung capacity.